(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the theoretical and practical aspects of organizing independent learning for students within the modular-credit system. The study analyzes the essence of the modular-credit system, its advantages, methods for effectively organizing independent learning, and assessment mechanisms. Based on local and international experiences, the article examines ways to improve students’ self-development activities. The research findings offer recommendations for enhancing independent learning and improving the quality of education within the modular-credit system.